Analisa Pola Perubahan Suhu Permukaan Menggunakan Google Earth Engine Berbasis Web Gis - Hermawan, Erwin; Agustian, Sahid; Wahyudi, Ikmal (Jurnal Etnik: Ekonomi-Teknik, 2023)
Development in an area must pay attention to the socio-economic conditions of the community such as the level of education, health and economic facilities as well as other factors. The development of this region cannot be separated from the regional spatial planning, this is very necessary to realize a balanced development. Bogor Regency is one of the regencies whose development is currently quite developed, the increase in population causes a reduction in land with vegetation cover to become built-up areas, from the increase in built-up land it causes an increase in temperature in Bogor Regency. Conditions like this can cause temperatures in urban areas to be much higher than in villages due to vegetation factors. From this background, how to analyze the pattern of changes in surface temperature using the GIS web-based Google Earth Engine in the Ciseeng, Gunung Sindur, Kemang, Parung, Parungpanjang, Rancabungur and Rumpin Districts. Therefore it is necessary to analyze the pattern of changes in surface temperature using the GIS web-based Google Earth Engine in the Ciseeng, Gunung Sindur, Kemang, Parung, Parungpanjang, Rancabungur and Rumpin sub-districts and create an information system about mapping surface temperature change patterns using the GIS web-based Google Earth Engine. . The results showed that the average surface temperature reached 25?C, this analysis used the Google Earth Engine in order to find out temperature changes in the Ciseeng, Gunung Sindur, Kemang, Parung, Parungpanjang, Rancabungur and Rumpin sub-districts in 2002, 2008, 2014 and 2019. With that, it can be seen that the highest temperature level was in 2008 with a temperature of 34?C.